Urban geometry parameters as indicators for urbanization effects : a case study in Paranhos, Portugal - Balkestahl, Licínia (2008)
We are convinced of that applied urban climatology can constitute a good life quality and sustainability indicator and can contribute to minimize/avoid situations of danger – or simply of absence of bioclimatic comfort – for the urban population. The area this urban climatology study is about (the parish of Paranhos - Porto - Portugal) grew substantially in the last fifty years, both concerning the quantitative population, the widening of the urbanized areas or the human activities, namely with the creation of a new University Pole. Based on the work done by T. R. Oke (Oke, 1978, 1987) and in order to improve the experimental knowledge of temperatures, we tried to evaluate, through the sky view factor (svf), how the urban geometry of Paranhos can be an external cause of the climatic subsystem, generating important contributions to changes in the behavior of temperature (thermal anomalies), especially in certain synoptic situations and in certain seasons. (...)